Evaluating budget accuracy in project-based logistics: A data-driven approach in global supply chain management - Suojanen, Elina (My University, 2025)
This thesis evaluates the accuracy of logistics budgeting in project-based business and examines factors contributing to budget deviations. The study was motivated by recurring discrepancies between planned and actual logistics costs, especially in projects involving complex supply chains and multiple ERP environments following a corporate merger. A case study approach was adopted, combining quantitative analysis of 752 projects completed between 2020 and 2024 with qualitative insights from internal documents and domain experts. Data were collected from ERP and Power BI systems, covering variables such as Incoterms, market region, and business line. To ensure reliability, the dataset was cross-verified, and measurement bias factors were considered. The findings reveal systematic underbudgeting, particularly in projects using FCA Incoterms, where logistics costs were often omitted from initial budgets despite actual expenses later occurring. Conversely, some projects showed significant overbudgeting, highlighting inconsistencies in forecasting practices. Differences across product groups, market regions, and business lines further suggest that logistics cost behavior is not uniform. The analysis also indicates that in projects with low sales value or low probability of being won, cross-functional budgeting reviews are not always conducted. In addition, in some cases internal logistics hours have not been recorded in SAP either due to incorrect hour bookings or because local guidance has not required the respective logistics team to book their hours. Logistics cost estimates rely on both historical project data and project-level market rate checks from LSPs, improving predictability of external costs. The transitional use of three ERP systems contributed to data inconsistencies, though the adoption of a new standardized SAP environment is expected to improve budgeting reliability. Practical recommendations include implementing region-specific budgeting templates, harmonizing WBS structures across business lines, introducing mandatory cost input fields in ERP systems, and promoting interdepartmental collaboration through joint budgeting checkpoints and post-project reviews. Overall, the study emphasizes the need for standardized, data-driven, and proactive logistics budgeting practices to reduce deviations, improve cost predictability, and strengthen financial control in project-based operations.

Tämä tutkimus arvioi projektipohjaisen liiketoiminnan logistiikkabudjetoinnin tarkkuutta ja tutkii budjettipoikkeamien taustalla olevia tekijöitä. Tutkimuksen taustalla olivat toistuvat erot suunniteltujen ja toteutuneiden logistiikkakustannusten välillä erityisesti monimutkaisissa toimitusketjuissa ja useiden ERP-järjestelmien käyttöympäristöissä yritysfuusion jälkeen. Tutkimus toteutettiin tapaustutkimuksena, jossa yhdistettiin määrällinen analyysi 752 projektista vuosilta 2020–2024 ja laadulliset havainnot sisäisistä dokumenteista ja asiantuntijahaastatteluista. Aineisto kerättiin ERP- ja Power BI -järjestelmistä, ja se sisälsi muuttujia, kuten Incoterms-toimitusehdot, markkina-alueen ja liiketoimintalinjan. Aineiston luotettavuutta varmistettiin ristiinvarmistuksilla ja mittausvirhelähteet huomioitiin analyysissä. Tulokset osoittavat järjestelmällistä alibudjetointia logistiikan osalta erityisesti FCA-toimitusehdon projekteissa, joissa logistiikkakustannuksia ei usein sisällytetty alkuperäisiin budjetteihin, vaikka toteutuneet kustannukset kirjattiin myöhemmin. Toisaalta joissakin projekteissa esiintyi myös merkittävää ylibudjetointia, mikä korostaa ennustamiskäytäntöjen epäyhtenäisyyttä. Eroja havaittiin myös tuoteryhmien, markkina-alueiden ja liiketoimintalinjojen välillä, mikä viittaa siihen, ettei logistiikkakustannusten käyttäytyminen ole yhtenäistä. Tuloksiin vaikutti myös se, että alhaisen myyntiarvon tai matalan voittotodennäköisyyden projekteissa monitoimijainen budjetointikatselmus ei aina toteudu, ja että joissakin projekteissa sisäisiä logistiikkatunteja ei ole kirjattu SAP:iin joko virheellisten tuntikirjausten vuoksi tai siksi, että paikallinen ohjeistus ei ole edellyttänyt tuntien kirjaamista. Logistiikan kustannusarviot perustuvat sekä historiallisten projektien tietoihin että projektikohtaisiin markkinahintojen tarkistuksiin LSP:iltä, mikä parantaa ulkoisten kustannusten ennustettavuutta. Kolmen eri ERP-järjestelmän rinnakkainen käyttö lisäsi aineiston epäjohdonmukaisuutta, mutta uuden SAP-järjestelmän käyttöönoton odotetaan parantavan budjetoinnin tarkkuutta jatkossa. Käytännön kehitysehdotuksia ovat aluekohtaiset budjetointimallit, WBS-rakenteiden yhdenmukaistaminen liiketoimintalinjojen välillä, pakolliset kustannuskentät ERP-järjestelmiin sekä osastojen välisen yhteistyön vahvistaminen yhteisillä budjetointitarkistuksilla ja projektien jälkiarvioinneilla. Tutkimus korostaa standardoitujen, dataohjattujen ja ennakoivien logistiikkabudjetointikäytäntöjen merkitystä poikkeamien vähentämisessä, kustannusten ennustettavuuden parantamisessa ja taloudellisen ohjauksen vahvistamisessa projektipohjaisessa liiketoiminnassa.
Keywords: supply chains; project management; logistics; budgeting; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management